Chitwan National Park: A Prime Destination of Eco-Tourism in Central Tarai Region, Nepal - Bhusal, Narayan P. (The Third Pole: Journal of Geography Education, 2009)
Within the Himalayan region, Nepal is one of the countries that receive the largest number of international tourists, and also one where tourism has shown relatively rapid growth. The recent decades in Nepal tourism is being explored as one of the avenues for local development and it is second important source of foreign exchange for Nepal. This paper is an attempt to present the brief description of tourism resources in general and Royal Chitwan National Park (but since the republic government in Nepal the name has been changed to Chitwan National Park and hereafter it is named only CNP) as an example of prime destination of eco-tourism in Nepal. Existing tourism activities and its environmental considerations have been discussed on the basis of available secondary and primary sources of information. DOI: http://dx.doi.org/10.3126/ttp.v5i0.1956 The Third Pole, Vol. 5-7, PP 70-75:2007